1966
DOI: 10.1677/joe.0.0350135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Early Thyroidal Iodide Clearance With Estimates Obtained at Later Intervals

Abstract: SUMMARY The rate of thyroidal iodide clearance has been measured repeatedly during the periods 2–20 min., 20 min.-2 hr., 2–10 hr. and 10–24 hr after i.v. administration of 131I Early measurements (after 2–20 min.) gave higher values than the estimates obtained at later, more conventional, periods. Treatment with carbimazole produced a slight decrease in the clearance when measured between 2 and 20 min., a more pronounced decrease when measured between 20 min. and 2 hr., and a decrease to virtually zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

1966
1966
1978
1978

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…The 1-dose was lower when the gland was hyperfunctional ; and correlation was observed with PIl, and hence presumably intracellular iodide concentration (210). Koutras and co-workers (212), following the earlier suggestion of Ingbar, subdivided thyroidal clearance into "unidirectional clearance" at two to twenty min utes after intravenous inj ection of 1311, and "net clearance" at two hours or more when loss of unbound 1* was complete (212). Koutras and co-workers (212), following the earlier suggestion of Ingbar, subdivided thyroidal clearance into "unidirectional clearance" at two to twenty min utes after intravenous inj ection of 1311, and "net clearance" at two hours or more when loss of unbound 1* was complete (212).…”
Section: Kinetic Studies Of Iodine Metabolismmentioning
confidence: 99%
“…The 1-dose was lower when the gland was hyperfunctional ; and correlation was observed with PIl, and hence presumably intracellular iodide concentration (210). Koutras and co-workers (212), following the earlier suggestion of Ingbar, subdivided thyroidal clearance into "unidirectional clearance" at two to twenty min utes after intravenous inj ection of 1311, and "net clearance" at two hours or more when loss of unbound 1* was complete (212). Koutras and co-workers (212), following the earlier suggestion of Ingbar, subdivided thyroidal clearance into "unidirectional clearance" at two to twenty min utes after intravenous inj ection of 1311, and "net clearance" at two hours or more when loss of unbound 1* was complete (212).…”
Section: Kinetic Studies Of Iodine Metabolismmentioning
confidence: 99%
“…However, Thomas et al (30) were probably the first who deliberately introduced the 10 min radioiodine uptake for studying thyroid function in patients receiving antithyroid drugs. This subject has been investigated more intensively by Koutras and Sfontouris (21), who showed that the early thyroidal iodide clearance rate (calculated between 2 and 20 min) resulted in systematically higher values than estimates obtained at later time intervals. These workers suggestend that the earlier the estimate, the more it corresponded to the theoretical "unidirectional" clearance, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Papadopoulos et al (26) have detected a small degree of intrathyroidal metabolism of pertechnetate, but this appears to be of little significance for early uptake measurements. The iodide trapped is also bound organically only in part (8,21), and so it seems that the difference between iodine and pertechnetate is quantitative rather than qualitative, but nevertheless considerable. Since the degree of organic binding of these isotopes is so different, it should be of interest to compare their thyroidal uptake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been claimed that early thyroid uptake measurements are unaffected by such drugs and that they can be used to measure the thyroid iodide concentrating mechanism or trap (Thomas et al, 1960;Koutras and Sfontouris, 1966). Whether or not this is so will depend on the rate at which trapped iodide becomes bound, on the time at which the measurement is made, and on the extent to which organic binding of iodine is impaired by the antithyroid drug.…”
Section: Discussionmentioning
confidence: 99%